Power in Jeopardy: A Poststructuralist Reading of the Arthurian Legend from Malory’s Le Morte d’Arthur and Tennyson’s Idylls of the King to Tolkien’s The Lord of the Rings - Edman, Timuçin Buğra (Journal of History Culture and Art Research, 2015)
Power in Jeopardy: A Poststructuralist Reading of the Arthurian Legend from Malory’s Le Morte d’Arthur and Tennyson’s Idylls of the King to Tolkien’s The Lord of the Rings Abstract The days of the classical heroes are over, as the days of Romance or Chivalric Romance and Epic that depict the hero in quest of the ideal are. A typical Romance situates the hero in a succession of challenges, each of which is overcome by him, who finally defeats the dark, evil force and brings peace and order to his community, thus offering to it the opportunity of living in a system defined by the norms of universal morality and enlightenment. The hero becomes a model of universal justice and stability, and he towers above all of his fellow men as a symbol of perfection and endurance of will against the powers of darkness. This plot of one-man challenge and task has been much fruitful in the creation of the stories of the pre-Christian times, the times of the foundation and expansion of Christianity, and the Medieval Age. During these eras such legendary figures as Osiris, Prometheus, Moses, Jesus Christ, and King Arthur of England have emerged as representative perfect super heroes and as universal and absolute role models. Known as monomyths, such stories have shown parallelism regarding the character and plot structure, all yielding similarities as dictated by Romance; this is mostly obvious through the continuous clash of good and evil. The clash creates a sustained tension in the reader whose moral understanding and conscience are kept busy in wondering whether the hero will lose the battle of righteousness or win it, announcing that human dignity has once again been victorious over evil forces. As suggested above, the days of such heroes are over, together with their references to super human qualities which have long been referred to as universal symbols that stand for ideal models for humanity. Such symbols, signifiers, refer to a sign both in Semiotics and Linguistics. Simply, it can be defined as something which has a meaning other than itself. Therefore, conventionally, a sign is assumed to transmit information to the one who understands or deciphers it1 and signified2 elements. Signifieds intended or ultimate logos to be reflected through signifier have become clichés. Henceforth, this situation hinders the creativity of the contemporary writer, John Ronald Reuel Tolkien, who has experienced both modernism and postmodernism. An updated deconstruction of Romance and Epic and their referents by J.R.R. Tolkien in his The Lord of the Rings is a strong anti-thesis of the old principles of authorship. The signifiers Tolkien uses do not yield a single conventional signified, although they refer to the sub-creation, in which unique characters and events were created in a peculiar world, that is, Middle-earth. Besides, Tolkien, inspired by Camelot and the Arthurian legends of both Sir Thomas Malory’s Le Morte d’Arthur and Alfred, Lord Tennyson’s Idylls of the King, deconstructs the conventional signifieds in his works.